The Effect of Motivation, Workload and Work Stress on Employee Performance Mediated by Work Satisfaction: The Case of RSUD Dr. (HC) Ir. Soekarno Bangka Belitung Island Province - Afserinta, Yusi; Djazuli, Abid; Choiriyah, Choiriyah (International Journal of Marketing & Human Resource Research, 2025)
The study examines the effect of motivation, workload and workstress on employee performance which is mediated by work satisfaction on employee performance at RSUD Dr. (HC) Ir. Soekarno Bangka Belitung Island Province. This research is also verification research (causal study). This research involves variables consisting of three independent variables, one dependent variable, and one intervening variable. The independent or exogenous variables contained in this study include work motivation (ξ1), workload (ξ2), and work stress (ξ3). The dependent or endogenous variable is employee performance (η2). At the same time, the intervening variable is job satisfaction (η1). The population used in this study were all employees at Dr. (H.C.) Ir. Soekarno Hospital has 320 permanent employees, excluding medical personnel. The number of samples in this study was 160 permanent employees. The sampling technique above used a probability sampling technique with accidental sampling. The analysis model used in this study was Structural Equation Modeling (SEM). The result reveals that the motivation, workload and workstress on employee performance which is mediated by work satisfaction on employee performance at RSUD Dr. (HC) Ir. Soekarno Bangka Belitung Island Province